An Analysis of the Content and Effectiveness of Off-Campus Internship curriculum for Vocational and Technical Five-Year Junior College Students with Major in Cosmetics - YEH, Ju-Hsuan; Lo, TSAI-YUN; Wang, LI-FENG (Advances in Social Sciences Research Journal, 2018)
The study objects comprise of vocational and technical schools in Taiwan and conducts group analysis on internship institutions, school teachers and students through qualitative research and quantitative research.The internship content reveals greatest difference for students’ performance in workplace etiquettes p< .001 while student’s workplace performance p < .01: Workplace skills, interpersonal communication and work attitude. Students’ workplace performance p < .05: adaptability issue, internship welfare, minor discretion in the presentation of internship agreement. With regards to learning factor analysis: The CR value is 0.913 and AVE value is 0.677 for interpersonal interaction and attitude learning, the CR value is 0.845 and AVE value is 0.577 for welfare regulations and career, and the CR value is 0.715 and AVE value is 0.457 environmental cognition and adaptability. A CR value greater than 0.7, suggests excellent internal consistency in the research model while AVE value also meets the standards.